The Effectiveness of Interactive Multimedia in Improving Motivation and Learning Outcomes of Junior High School Physical Education Students: The Effectiveness of Interactive Multimedia in Improving Motivation and Learning Outcomes of Junior High School Physical Education Students - Khasanatul Barikah; Imam Hariadi; Rajip Mustafillah Rusdiyanto (S&Co Publishing, 2026)
Abstracts: The integration of interactive multimedia in Physical Education, Sports, and Health (PJOK) learning at the junior high school level has become increasingly important in response to advances in educational technology. This study aims to systematically examine the effectiveness of interactive multimedia in enhancing students’ learning motivation and learning outcomes in PJOK. A Systematic Literature Review (SLR) was conducted following the PRISMA guidelines. Relevant articles were retrieved from Google Scholar, Garuda, ResearchGate, and ScienceDirect, covering publications from 2021 to 2025. Studies that met the inclusion criteria were analyzed using a thematic analysis approach. The findings indicate that various forms of interactive multimedia, including digital learning applications, interactive e-modules, and instructional videos, consistently have a positive impact on students’ learning motivation, cognitive understanding, and motor skill acquisition. The effectiveness of interactive multimedia is strongly influenced by the alignment between media design, instructional objectives, and the characteristics of PJOK learning materials. This review concludes that interactive multimedia represents an effective and adaptive instructional approach for supporting PJOK learning at the junior high school level. The results of this study are expected to provide practical insights for physical education teachers in designing technology-enhanced learning and to serve as a foundation for future research with broader scope and longer implementation periods.